Architectural Complex of the Pochinok State Stud Farm in the 17th-20th Centuries - M. S. Sukhanov; A. N. Garashchenkova (Научный диалог)
The article is devoted to the study of the problem of monuments of regional importance restoration by the example of the architectural complex of the Pochinkovskiy state stud farm. The information on the stages of the ensemble formation of the stud farm is presented. The authors pay special attention to the analysis of planning and stylistic features of the production and residential parts of the complex, the characteristics of the infrastructure developed on its territory. Examples of structural transformation of individual structures are given, as a result of which their original functional purpose has changed. It is proved that the architectural ensemble of the Pochinkovsky stud farm played a town-forming role in the structure of the same-named settlement. The authors emphasize the high level of development of Russian architectural thought in the XIX century, in which even provincial production complexes turned into monumental monuments, characterized by functional clarity and regularity of forms in combination with artistic expressiveness and non-standard architectural solutions. The novelty of the study is due to the use of an integrated approach to recreating the original appearance of the historical and architectural monument. The article continues the development of scientific ideas about the role of the stud farm in the process of forming planning and stylistic features in the structure of the settlement of Pochinki.